2022
DOI: 10.3390/plants11141815
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Molecular, and Biochemical Characterization of a Unique Lentil (Lens culinaris Medik.) Genotype Showing Seed-Coat Color Anomalies Due to Altered Anthocyanin Pathway

Abstract: This study reports the identification of a unique lentil (Lens culinaris Medik.) genotype L4717-NM, a natural mutant (NM) derived from a variety L4717, producing brown, black, and spotted seed-coat colored seeds in a single plant, generation after generation, in different frequencies. The genetic similarity of L4717 with that of L4717-NM expressing anomalous seed-coat color was established using 54 SSR markers. In addition, various biochemical parameters such as TPC (total phenolic content), TFC (total flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 99 publications
0
5
1
Order By: Relevance
“…The seed size, color, and testa appearance of lentils are important grading factors influencing the nutritional quality [ 7 ] and market acceptance [ 9 , 10 ]. In this study, we developed a new computer vision system for assessing the seed size, color grading, and testa morphology of lentils using an off-the-shelf mobile phone camera to acquire the images of the 64 pigmented lentil genotypes obtained from the International Center for Agricultural Research in the Dry Areas (ICARDA-Lebanon).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed size, color, and testa appearance of lentils are important grading factors influencing the nutritional quality [ 7 ] and market acceptance [ 9 , 10 ]. In this study, we developed a new computer vision system for assessing the seed size, color grading, and testa morphology of lentils using an off-the-shelf mobile phone camera to acquire the images of the 64 pigmented lentil genotypes obtained from the International Center for Agricultural Research in the Dry Areas (ICARDA-Lebanon).…”
Section: Discussionmentioning
confidence: 99%
“…A first step to guarantee their preservation is to characterize them both in situ and ex situ starting from the grain seed size, which is one of the major qualitative descriptors of lentil [ 5 ]. Besides grain size, grain color is another important morphological trait associated with quality [ 6 , 7 ]. In particular, grain color is given by the grain ground color (i.e., green, grey, brown, black, or pink), the cotyledon color (i.e., yellow, orange, red, or olive green), the pattern of testa (i.e., absent, dotted, spotted, marbled, or complex), and the color of pattern on testa (absent, olive, grey, brown, or black) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of seed-coat color in legume nodulation has been established [ 6 , 15 , 16 , 17 , 18 ], little is known about its influence on the choice of rhizobia by legumes for symbiotic partnership, root nodulation, and N contribution. Darker seed-coat color is reported to contain greater levels of flavonoids, anthocyanins, and anthocyanidins that promote superior symbiotic functioning [ 17 , 19 ]. Hungria and Phillips [ 17 ] and dos Santos Sousa [ 20 ] have, in fact, shown that common bean ( Phaseolus vulgaris L.) seedlings generated from a black-seeded genotype formed more root nodules compared with its white isogenic counterpart.…”
Section: A Historical Perspective On Legume Seed-coat Pigmentationmentioning
confidence: 99%
“… Yellow Higher water absorption [ 88 ] Adzuki bean ( Vigna angularis L.) Black Higher accumulation of anthocyanins [ 89 , 90 ] Lentil ( Lens culinaris Medik.) Black Higher nutraceutical values [ 19 ] Peanut ( Arachis hypogaea L.) Dark red Higher polyphenol content [ 91 ] Kersting’s groundnut ( Macrotyloma geocarpum Harms) Black Higher nitrogen fixation [ 41 ] …”
Section: Grain Legume Seed Coats Are a Natural Source Of Nutraceutica...mentioning
confidence: 99%
“…(2007) noted reduced damage during handling in the rounder seed-shaped lentil cultivars over thin, sharp-edged types. Thus, the development of genotypes with improved seed parameters including seed weight is an important breeding objective of lentil breeders across the globe ( Mishra et al., 2022b ). Generally, seed parameters are measured using crude phenotypic evaluation methods like measurement of 100-grain weight or seed diameter measurement using Vernier caliper or graded sieve ( Hossain et al., 2010 ; Xu et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%